STRENGTHENING HISTORICAL THINKING SKILLS THROUGH TRANSCRIPT BASED LESSON ANALYSES MODEL IN THE LESSON OF HISTORY - Abbas, Ersis Warmansyah; Syaharuddin, Syaharuddin; Mutiani, Mutiani; Susanto, Heri; Jumriani, Jumriani (ISTORIA : Jurnal Pendidikan dan Ilmu Sejarah, 2022)
Strengthening historical thinking skills is needed in History subjects. This skill is eductive so that students can describe the chronology of events based on historical facts. Observations on subjects are needed to improve historical thinking skills, namely by implementing lesson study (ls) activities. This article aims to describe the strengthening of historical thinking in history learning through the LS activity of the Transcript Based Lesson Analysis (TBLA) model. The approach through the descriptive method is used in research. Three stages of data collection, namely; observation, interview, and documentation. Miles and Huberman's model is used for analyzing the saturation of the data obtained. Results describe students can demonstrate historical thinking skills by providing arguments during group discussions. The arguments are given to put forward the causal relationship (causality) in the sub-discussion ABRI's dual function. Transcript analysis of overall learning activities illustrates that there is a balance of conversation between teachers and students. This is because the learning conditions are conducive and teachers have no difficulty in increasing the participation of studentsKeywords; historical thinking, TBLA, and History learning